2007
DOI: 10.1002/rra.1026
|View full text |Cite|
|
Sign up to set email alerts
|

Salmonid observations at a Klamath River thermal refuge under various hydrological and meteorological conditions

Abstract: The Beaver Creek confluence with the main-stem Klamath River was studied to assess salmonid use in a thermal mixing zone under various summer hydrological and meteorological conditions. Main-stem flow releases from Iron Gate Dam ranged from 17 cms (615 cfs) to 37 cms (1320 cfs) during the study period and main-stem water temperatures ranged from 19.5 to 268C. A grid was constructed to define the thermal refuge as a system of cells. Temperatures were monitored using remote temperature loggers and fish counts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 21 publications
6
86
0
Order By: Relevance
“…In particular, mainstem temperature was the strongest predictor of juvenile steelhead refuge use, with .80% of fish entering refuges when the mainstem reached 228C. These results are consistent with observational studies on salmonid use of thermal refuges in both the Klamath and other systems, which found that juvenile steelhead and coho salmon moved into refuges when mainstem temperatures reached 22-238C (Nielsen et al 1994, Sutton et al 2007). However, fish body temperatures indicate that some individuals were still utilizing mainstem habitat up to approximately 258C, the temperature at which bioenergetics predictions for steelhead specific growth rate drops towards zero (Hanson et al 1997, Beauchamp 2009).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In particular, mainstem temperature was the strongest predictor of juvenile steelhead refuge use, with .80% of fish entering refuges when the mainstem reached 228C. These results are consistent with observational studies on salmonid use of thermal refuges in both the Klamath and other systems, which found that juvenile steelhead and coho salmon moved into refuges when mainstem temperatures reached 22-238C (Nielsen et al 1994, Sutton et al 2007). However, fish body temperatures indicate that some individuals were still utilizing mainstem habitat up to approximately 258C, the temperature at which bioenergetics predictions for steelhead specific growth rate drops towards zero (Hanson et al 1997, Beauchamp 2009).…”
Section: Discussionsupporting
confidence: 85%
“…Juvenile steelhead rear in the river for 1-3 years before out-migrating to the ocean. During summer months the mainstem reaches temperatures that can be thermally inhospitable to salmonids-mean daily mainstem temperatures at the study sites ranged from 148 to 268C between 2010 and 2012-and juveniles seek out thermal refuges, usually at tributary confluences (Sutton et al 2007 (Pike et al 2013). The number of study sites sampled varied across years (sites 1-4 in 2010; sites 1-3 in 2011; site 1 in 2012) due to access issues (landowner permission) and the number of radio tags available.…”
Section: Study Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Several anadromous salmon species that return to spawn each year in this region do so during the summer period when average temperatures and seasonal extremes (i.e., MaxWATs) are warming most rapidly. In some instances, these migrations are now periodically disrupted during especially warm periods as the fish pause to congregate near coldwater sources (Goneia et al 2006;Sutton et al 2007;Keefer et al 2009) and fish that migrate during the year's warmest temperatures often return less successfully to their spawning areas (Cooke et al 2004;Keefer et al 2008). Thermal "events" wherein hundreds or thousands of adult salmon die simultaneously because thermal tolerances are exceeded have been documented in recent years (Lynch andRisley 2003, Doremus andTarlock 2008;Keefer et al 2010) and important recreational fisheries are now sometimes suspended during warm periods to minimize additional fish stress (Brick et al 2008).…”
Section: Implications For Salmonid Fishesmentioning
confidence: 99%
“…In rivers, temperature exerts an important control on physiochemical characteristics of water [15] and it is a driver of Water 2017, 9, 358 2 of 16 numerous biological processes, controlling the structure of ecological communities and habitat complexity [16,17]. Approaches for measuring stream water temperature cover a wide range of methods including temperature loggers and thermometers [18][19][20], fiber-optic distributed temperature sensing (FO-DTS) [21,22] and thermal infrared (TIR) cameras [23][24][25].…”
Section: Introductionmentioning
confidence: 99%